(untitled) (Scientific journal of the Fergana State University, 2025)
The current state of livestock breeding in our three republics and the importance of feeding in controlling their productivity are described. One of the most profitable products in animal husbandry, the production of energy sources in specialized production and the transfer of resources through the environment in high-quality and low-cost products, this intensive hydroponics has the potential to produce blue income.